Implementasi Sistem E-Learning Berbasis Web sebagai Upaya Digitalisasi Pembelajaran di SMK Islam Iqro - Eko Nugroho, Aditya; Nizar Fazari, Ma’ruf; Jupron (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
The learning process at SMK Islam Iqro was still conducted conventionally, making material distribution, attendance recording, assignment submission, and quizzes entirely reliant on paper-based manual methods. This condition led to time inefficiency, difficulty in monitoring students’ learning progress, and limited access to academic information outside school hours. This study aims to design and implement an integrated web-based e-learning system to support the digitalization of the learning process at SMK Islam Iqro. The system was developed using the Waterfall method, encompassing analysis, design, implementation, and testing phases. The technology stack comprised native PHP, MySQL as the database, and an interface built with HTML, CSS, and JavaScript. The system accommodates three user roles Admin, Teacher, and Student each with access rights managed through Role-Based Access Control (RBAC). Core features include learning material management, digital attendance, assignment management, automated quiz grading, a discussion forum, and a notification system. Testing was conducted using the Black Box Testing method across ten functional scenarios, all of which produced results consistent with expected outputs, confirming that the system operates correctly without technical issues. The implementation successfully transformed manual workflows into digital processes, improved the management efficiency of teaching and learning activities, and provided real-time academic information access for all stakeholders within the school environment.